Review of scoping studies on service quality, customer satisfaction and customer loyalty in the airline industry - Virginia Simón-Moya (Contemporary Economics, 2019)
The paper studies a method for evaluating current literature that receives little consideration in research and development. Various types of undervalued studies are recognized, and how they are related to a systematic review is shown. A diagram is presented that illustrates scoping studies reviews and their impacts on satisfaction. Finally, this paper examines the favorable circumstances and impediments surrounding this methodology and recommends a more extensive discussion to clarify the relationship between scoping studies and other study types found in reviews of literature. This study additionally aims to determine the effects of price sensitivity and quality seekers on products. It also aims to discern the level of customer loyalty to certain airline brands. The literature review uncovered that the airline industry is increasingly focusing on growing top notch services to compete in the market. In addition, competition in this sector is apparent in the evaluation and the type of services offered. The study embraces these two perspectives (price sensitivity and quality seekers) as directing viewpoints in the system of relationship.
Keywords: L6; L7; L15; Z21; 330; Service quality; Customer satisfaction; Customer loyalty; Airline industry